The Effectiveness of Integrating Smart Board and Metacognitive Skills on Knowledge Achievement Related to Instructional Courseware Production Skills among Instructional Technology Students - Jbeili, Ibrahim Jbeili (Jordan Journal of Educational Sciences, 2014)
The current study investigates the effectiveness of integrating smart board and metacognitive skills on achievement related instructional courseware production skills among technology Department students. The sample consists of (50) bachelor male and female scholars from instructional technology department at Jadara University in Jordan. Two classes of "Instructional Courseware Production" were randomly selected. The two classes were randomly assigned as experimental group and control group. The experimental group comprised of (25) participants who used the smart board and employed the metacognitive skill. The control group comprised of (25) participants who used the smart board without metacognitive skills. At the end of experiment that lasted six week, an achievement test was conducted. The results showed that participants in the experimental group significantly outperformed participants in the control group. Based on the study results, a set of recommendations were formulated